¿Nuevos problemas, viejas palabras? La traducción del discurso anticomunista en América Latina: el caso del V Foro Atlántico de la Fundación Internacional para la Libertad (2008) - María Julia Giménez; André Kaysel (Les Cahiers de Framespa)
This article studies how liberal right wingers in Latin America in the 21st century have resurrected the anticommunist vocabulary of the Cold War by looking at the V Fórum Atlántico which was promoted by the Fundación Internacional para la Libertad in Madrid (2008). Using Gramscian reflections on translation and Peter Burke’s writings on the "culture of translation", this article demonstrates how the conference participants condemned the Socialist regime in Cuba and how they updated traditional anticommunist arguments in the context of the surge of so-called “pink tide” governments in Latin America.